The International Conference on Applied Science and Health (ICASH): Promoting future health: Excellence, relevance and cost benefit - Andrew John Macnab (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Not required